Surgical duration is associated with an increased risk of periprosthetic infection following total knee arthroplasty: A population-based retrospective cohort study - Ravi, Bheeshma (EClinicalMedicine, 2019)
BACKGROUND: Total knee arthroplasty (TKA) is one the most common elective procedures in the world. Post-operative infection is one of its most devastating complications, often necessitating multiple additional surgeries. We aimed to describe the relationship between surgical duration and risk of deep infection following primary elective TKA. METHODS: In this cohort study we analyses primary TKAs done between 2009 and 2016 in Ontario, Canada. We utilized restricted cubic splines to identify a threshold of surgical duration that was associated with an increased risk for infection requiring surgery. Patients with a ‘short’ duration of surgery were matched to those with a ‘long’ duration on patient age (±3 years), patient sex, severe obesity (BMI > 40), the primary surgeon, the hospital and the type of anesthetic. FINDINGS: In 92,343 primary TKAs, the median surgical duration was 106 min. We identified a cut-point of 100 min that was associated with an increased risk for infection. Subsequently, 17,815 TKA recipients with a ‘long’ procedure length were matched to those with a ‘short’ procedure length. ‘Long’ procedures had a higher rate of deep infection (1.1% versus 0.6%, p < 0.0001). This was equal to a relative risk of 1.81 (p < 0.0001). INTERPRETATION: In a cohort of TKA recipients, we found that procedure lengths longer than 100 min were associated with a significantly increased risk of deep infection requiring surgery. This time threshold serves a useful time-point to identify patients that require closer surveillance.